A cowgirl's story [videorecording (DVD)] - Armstrong, Tim; Madison, Bailee, 1999-; Boone, Pat; Lukasiak, Chloe (Sony Pictures Home Entertainment, 2017)
The story of high school cowgirls who must hold down the home front while their military parents are on duty in Afghanistan.